What drives loan losses in Europe? - Esa Jokivuolle; Jarmo Pesola; Matti Virén (Bank of Finland, 2014)
We model banks' loan losses with a panel of European countries for the period 1982-2012 using three country-specific macro variables: output growth shocks, real interest rates, and a measure of excessive private sector indebtedness. We find that a drop in output has an intensified impact on rising loan losses if the economy is excessively indebted. This may explain differences in loan losses in different recessions across time and across countries. For instance, the dramatic output drop in Finland in 2009 did not cause large loan losses compared with the Finnish crisis of the early 1990s because of the more moderate level of indebtedness. Low interest rates during the recent recession may have been another, perhaps the most important, factor mitigating loan losses.
URN:NBN:fi:bof-20140807672
Keywords: E44; G28; 330; loan losses; banking crises; indebtedness